Understanding School Success of Migrant Students: An International Perspective - Makarova, Elena; Kassis, Wassilis (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The aim of this book is to empirically identify the school success pathways of migrants for policy actions in schools and communities in order to tackle barriers to migrant students' school success. These resilience pathways highlight differences in individual and social risks and identify protective factors for young migrants to overcome obstacles linked to discrimination and low educational outcomes. It presents international empirical research comparing and explaining school success factors for migrant students in various countries, namely, Germany, Greece, Russia, and Switzerland.